Development of Mild Strains of Papaya Ringspot Virus-Papaya Strain - Mowlick, S; Akanda, AM; Rahman, AHMA (Journal of Agriculture & Rural Development, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> An attempt was made with BARI papaya-1 to develop the mild strains of Papaya ringspot virus-papaya strain (PRSV-P) to use in cross protection. Three mutagents (viz. nitrous acid, sodium azide and UV radiation) with different concentrations and exposure time were used in this experiment. Mutagenic treatments of extraction of PRSV-P infected sap with 0.075M nitrous acid, 2% sodium azide, and exposure to UV radiation for 1 and 2 minutes were observed to be the best in the production of effective mild strains of PRSV-P. The mild strains of PRSV-P containing papaya seedlings were faced to challenge inoculation test. It was observed that younger seedling condition delayed the virus infection as compared to older ones. Key words: PRSV-P, mutagenic treatments, cross protection. DOI = 10.3329/jard.v5i1.1464 J Agric Rural Dev 5(1&2), 94-97, June 2007